2015
DOI: 10.1194/jlr.p052217
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic changes of LDL in overweight and moderately hypercholesterolemic subjects taking phytosterol- and omega-3-supplemented milk

Abstract: The prevalence of overweight and obesity is increasing and represents a primary health concern due to the relationship between obesity and a number of diseases and comorbidities including hyperlipidemia, a major risk factor for atherosclerosis and CVD. Dyslipidemias, typically characterized by high serum LDL cholesterol (LDLc), or low levels of HDL cholesterol (HDLc), and/or elevated triglyceride (TGL) levels, are common among patients with established CVD, type 2 diabetes mellitus, and the metabolic syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 62 publications
(51 reference statements)
2
43
1
Order By: Relevance
“…Particularly, a strong correlation was found for the PC32:0 subclass. We found a reduction in PC32:0 in those individuals under the phytosterol milk intervention as well as in PC34:1, a highly abundant PC in LDL particles . The fact that the strongest coordinated changes after phytosterol‐enriched milk were observed between PC metabolites differing by two carbon atoms in their fatty acid side chain suggests that changes result from products of elongation processes occurring in the LDL after the dietary intervention.…”
Section: Dietary Patterns and Functional Foods With Beneficial Propermentioning
confidence: 75%
See 2 more Smart Citations
“…Particularly, a strong correlation was found for the PC32:0 subclass. We found a reduction in PC32:0 in those individuals under the phytosterol milk intervention as well as in PC34:1, a highly abundant PC in LDL particles . The fact that the strongest coordinated changes after phytosterol‐enriched milk were observed between PC metabolites differing by two carbon atoms in their fatty acid side chain suggests that changes result from products of elongation processes occurring in the LDL after the dietary intervention.…”
Section: Dietary Patterns and Functional Foods With Beneficial Propermentioning
confidence: 75%
“…Another important finding of our study was the detected decrease in LDL susceptibility to oxidation after intake of phytosterol-enriched milk [40]. The susceptibility of LDL to oxidation has been linked to their content in sphingomyelines, lipid components reported as physiological inhibitors of lipoprotein oxidation due to their effects in LDL surface fluidity and propagation of the oxidation reaction in the PC monolayer [42].…”
Section: Figurementioning
confidence: 83%
See 1 more Smart Citation
“…LDL, particularly when 34 modified, also stimulate several atherogenic processes, such as interleukin-8 (IL-8) secretion 35 of endothelial cells, which induce the chemotactic recruitment of monocytes to the arterial 36 intima [1,9,10]. Modified lipoproteins are taken up by macrophages, which leads to foam- 37 cell formation. Retained and modified lipoproteins and foam cell formation leads to the 38 release of proinflammatory cytokines and bridging molecules (e.g.…”
mentioning
confidence: 99%
“…In these studies, changes in the LDL lipidome were induced 300 enzymatically and increased content of free fatty acids and lysophosphatidylcholine was 301 found to enhance IL-8 release. Instead, studies investigating dietary effects on LDL lipidome 302 are scarce [8,37], and to our knowledge, there are no previous studies investigating the 303 effects of dietary intervention on inflammatory properties of LDL particles. Padro et al [37] 304 found that milk enriched with long-chain n-3 PUFA (0.375 g/250 ml milk) did not induce 305 changes among lipid species of LDL.…”
mentioning
confidence: 99%